(untitled) (Revista Argentina de Cirugía, 2022)
Objetive: Report the frequency of bile duct stones in different age groups. Method: A retrospective review of all patients scheduled for cholecystectomy, in the period elapsed between May 1992 to May 1998, in whom intraoperative cholangiography could be done was presented. They were divided into seven groups according to age. Gl < 30 years old, G2: 30 - 39 years old, G3: 40 - 49 years old, G4: 50 - 59 years old, G5: 60 - 69 years old, G6: 70 - 79 years old, G7: 80 years or older. The frequency of bile duct stones was established. Statistic analysis were done in the Arcus Quickstat Biomedical program. Results: 879 patients were included. Average age was 59 years old. Females were 72%. Bile duct stones were found in 133 patients (15.1%). The frequency of bile duct stones was 21% in Gl, between 3% and 7% in groups 2-4, 15.4% in G5, 22.4% in G6 and 50% in G7. Conclusions: There are differences in the frequency of presentation of bile duct stones, and they are related to age. There is a bimodal tendency of distribution with peaks in the extremes of life. It duplicates for decades over sixty years old.